Cover Feature: Engineering Artificial Fusion Proteins for Enhanced Methanol Bioconversion (ChemBioChem 23/2018). (16th November 2018) - Fan, Liwen; Wang, Yu; Tuyishime, Philibert; Gao, Ning; Li, Qinggang; Zheng, Ping; Sun, Jibin; Ma, Yanhe
Abstract : The cover feature picture shows three legendary warriors, from the famous Chinese novel Three Kingdoms, who are taking an oath together in a peach garden. Three fused methanol bioconversion enzymes catalyze the transformation of C1 to Cn more efficiently than individual ones, just like the three sworn brothers achieves greater things in their dynasty. With this fusion‐engineering strategy, the efficiency of cascade reactions can be enhanced. More information can be found in the full paper by P. Zheng, J. Sun, et al. on page 2465 in Issue 23, 2018 (DOI: 10.1002/cbic.201800424 ).